Analisis Pengaruh Good Corporate Governance (GCG) terhadap Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) di Bursa Efek Indonesia - Hayer, Bienvenido G.B.; Saudira, Rania Aisya (Anthology: Inside Intellectual Property Rights, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) on the company's financial performance before and after the Initial Public Offering (IPO) on the Indonesia Stock Exchange. GCG is measured through indicators of managerial ownership, institutional ownership, proportion of independent commissioners, and audit committee. Financial performance is proxied by Return on Asset (ROA), Return on Equity (ROE), and Price Book Value (PBV). This study uses secondary data from the financial statements of companies conducting IPOs within a certain period, and regression analysis and t-test are conducted. The results show that the implementation of GCG generally has a positive influence on financial performance, especially after IPO, although not all GCG indicators have a significant effect partially. This finding confirms the importance of GCG implementation in improving firm performance and value, especially in the face of changes in ownership structure and transparency after IPO.